Environmental policies in local and international business : Example of Mexico - Yáñez Utrilla, Luis Carlos; Lisa, Aleš, 1956-; Dvořák, Antonín; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The purpose of this thesis is to examine the interplay between environmental policies and businesses, arguing that these policies should be viewed as opportunities rather than restrictions. Through a comprehensive analysis, the research investigates various aspects of environmental policies, demonstrating how they stimulate innovation, encourage sustainable practices, and promote corporate social responsibility. It argues that businesses can increase their long-term sustainability, build stakeholder trust, and contribute significantly to the worldwide effort towards environmental sustainability by aligning themselves with and embracing environmental policies. The thesis focused on various key terms and concepts that are relevant to environmental sustainability, corporate social responsibility, circular economy, and compliance. The discussion also covered the importance of engaging with stakeholders, adopting the triple-bottom-line approach, and using renewable energy sources. The emphasis was on the positive impacts of proactively implementing environmental policies, such as reducing carbon footprint, adapting to climate change, and achieving sustainable development goals. These discussions support the thesis's central argument that considering environmental policies as opportunities instead of constraints is not only ethical but also beneficial for businesses in navigating the complex terrain of global commerce.
Vedoucí práce: Aleš Lisa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses